Modeling of three phase inverter for photovoltaic application - Dharmaraj, Philips (2012)
A three-phase inverter for photovoltaic application is developed and simulated using MATLAB/Simulink software. By assuming the PV module is ideal at all weather condition, a basic dc source is used as input for the DC-DC closed loop step up converter. A pulse generator takes the role of an MPPT. The switching frequency is in the range of 500 MHz to 1 GHz at various duty cycles. This output is then used to switch IGBT inverter at 120° conduction mode. PWM Generator is used to generate pulses for carrier-based two-level pulse width modulator (PWM) in bridge converter. This block generates pulses for carrier-based pulse width modulation (PWM) converters using two-level topology. The block can be used to fire the forced-commutated devices three-phase bridges. The modulation index is set at 0.6-0.95, while the frequency is set in rad/sec. The sampling time is in the range of microseconds. The performance of the system is then further analyzed and proven by calculating the load current, inductance, impedance, load power, phase voltage and line voltage.